Sistem Penunjang Keputusan Pemilihan Pekerjaan Menggunakan Metode Profile Matching - Hamdan Arfandy; Erik Wijaya; Izmy Alwiah Musdar (AGENTS: Journal of Artificial Intelligence and Data Science, 2023)
The aim of this research is to design a decision support system for job selection. Finding job is the primary goal for students after graduation. The problem that arises is that many alumni are unaware and still confused about which field of work to pursue. In this study, a web-based decision support system was developed with the intention of being accessible via desktop and mobile devices. The Profile Matching method is utilized to generate job recommendations for system users. The application development employed the Bootstrap framework to ensure a more organized web interface. System testing was conducted using the black box method with twenty-five test cases. The result of this research is the successful development of a decision support system for job recommendations, which has undergone the system testing process. The testing results indicate that the system functions properly according to the system specifications, and no calculation errors or ranking discrepancies were found in the decision outputs displayed by the system.